2020
DOI: 10.1002/dta.2897
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of new psychoactive substances in blood samples of German drivers suspected of driving under the influence of drugs

Abstract: Driving under the influence of drugs (DUID) is a serious global problem and poses a public health risk. With new psychoactive substances (NPS) entering the illicit drug market several years ago, a significant number of highly potent and harmful drugs have become easily available and the use of these substances may impair a person's ability to drive a vehicle safely. Since NPS are not usually covered in routine toxicological analyses used in DUID investigations, only little is known about their prevalence. To g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Detailed information is described in Table 1 and in Table A of Supplementary material for human and animal studies collected, respectively. Additionally, 13 articles reported cases of DUI of SCs (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). Papers focused on humans tested several domains related to safe driving, which included cognitive and integrative functions (visuospatial and executive functions, attention, memory, planning, information processing speed, response inhibition), emotional processing and motor performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed information is described in Table 1 and in Table A of Supplementary material for human and animal studies collected, respectively. Additionally, 13 articles reported cases of DUI of SCs (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). Papers focused on humans tested several domains related to safe driving, which included cognitive and integrative functions (visuospatial and executive functions, attention, memory, planning, information processing speed, response inhibition), emotional processing and motor performance.…”
Section: Resultsmentioning
confidence: 99%
“…However, it allows an untargeted screening involving emerging compounds ( 80 ). By using LC-QTOF-MS coupled with LC-MS/MS, Fels et al found the presence of SCs in 12 of 837 blood samples collected from suspected German DUI cases in 2017–2018 ( 59 ). Similar results are described in literature from samples obtained during police checks or following road accidents ( 56 , 57 , 60 , 61 , 63 ), making it possible to ascertain that SCs consumption while driving is a widespread reality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LC-MS/MS analysis for detecting synthetic cannabinoids was performed on an Agilent 1290 Infinity system (Agilent Technologies), coupled to a QTRAP 6500 + system (Sciex, Darmstadt, Germany), and operated in sMRM mode with positive ESI. The method is described in detail elsewhere [27]. Briefly, chromatographic separation was achieved on a Kinetex C 18 reversed-phase column (3.0 × 50 mm, particle size 2.6 µm) (Phenomenex, Aschaffenburg, Germany).…”
Section: Lc-ms/ms Analysis For the Detection Of Synthetic Cannabinoidsmentioning
confidence: 99%
“…For all these reasons, SSA and NTA are now widely used for chemical analysis of environmental samples, although targeted analysis is still needed as a complementary method for unequivocal identification and more accurate quantification. However, full-scan HRMS also enables the re-analysis of data when the initial data processing workflow has been insufficient [22] or to retrospectively find newly identified or regulated compounds from other studies [23] . This becomes even more useful when the acquisition is performed using full-scan tandem mass spectrometry in data-dependent (DDA) or data-independent (DIA) analysis modes [24] .…”
Section: Introductionmentioning
confidence: 99%